2014
DOI: 10.1021/cm504029j
|View full text |Cite
|
Sign up to set email alerts
|

Viruslike Nanoparticles with Maghemite Cores Allow for Enhanced MRI Contrast Agents

Abstract: Here, for the first time, we demonstrate formation of virus-like nanoparticles (VNPs) utilizing gold-coated iron oxide nanoparticles as cores and capsid protein of brome mosaic virus (BMV) or hepatitis B virus (HBV) as shells. Further, utilizing cryo-electron microscopy and single particle methods, we are able to show that the BMV coat on VNPs assembles into a structure very close to that of a native virion. This is a consequence of an optimal iron oxide NP size (∼11 nm) fitting the virus cavity and an ultrath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…This is highly comparable to the clinically used MRI contrast agent such as Feridex 105 mM −1 s −1 65 , which shows noticeable changes after injecting iron oxide NPs 66 . Therefore this confirmed that the Au nanoshell around Nk did not play a role in Nk core spin 67 . But the r 2 value with Hep2 cells showed significant increment when compared to L6 cells because of gold iterations.…”
Section: Resultssupporting
confidence: 62%
“…This is highly comparable to the clinically used MRI contrast agent such as Feridex 105 mM −1 s −1 65 , which shows noticeable changes after injecting iron oxide NPs 66 . Therefore this confirmed that the Au nanoshell around Nk did not play a role in Nk core spin 67 . But the r 2 value with Hep2 cells showed significant increment when compared to L6 cells because of gold iterations.…”
Section: Resultssupporting
confidence: 62%
“…14, 20 Additionally, fundamental understanding of the interactions involved in particle self-assembly informed the fabrication of novel imaging agents (see Section 4.1.2 ). 21, 22 Through multidisciplinary collaboration, the use of viral scaffolds as unique materials for diverse applications can be realized.…”
Section: Viruses In a Materials Worldmentioning
confidence: 99%
“…Over the years a variety of protein cages, in particular viruses, have been studied for their application in nanotechnology, which has yielded knowledge about their biological, chemical, and physical properties . Due to their diversity, homogeneity, and well‐defined dimensional properties, there is increasing interest in the use of viruses or virus‐like particles (VLPs), for example, in the fields of biomedicine, materials science, and nanotechnology . Some examples of this work involve encapsulating non‐native cargo such as enzymes, polymers, or metal nanoparticles .…”
Section: Introductionmentioning
confidence: 99%